2013
DOI: 10.1007/s11920-013-0365-4
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Psychiatry Review: Differential Diagnosis and Treatment of the 3 D’s - Delirium, Dementia, and Depression

Abstract: The three D's of Geriatric Psychiatry-delirium, dementia, and depression-represent some of the most common and challenging diagnoses for older adults. Delirium is often difficult to diagnose and treatment is sometimes controversial with the use of antipsychotic medications, but it is common in a variety of patient care settings and remains an independent risk factor for morbidity and mortality in older adults. Dementia may affect a significant number of older adults and is associated with delirium, depression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 65 publications
1
46
0
1
Order By: Relevance
“…Signs and symptoms that can be useful to distinguish delirium from dementia are listed in Table 1. 3, 19, 20 Most prominently, with delirium, the onset is typically abrupt over hours to days, whereas with dementia the onset is insidious and progressive over months to years. With delirium, attention and level of consciousness are reduced and fluctuating; with dementia these domains typically remain intact until the advanced stages of dementia.…”
Section: Distinguishing Delirium From Dementiamentioning
confidence: 99%
“…Signs and symptoms that can be useful to distinguish delirium from dementia are listed in Table 1. 3, 19, 20 Most prominently, with delirium, the onset is typically abrupt over hours to days, whereas with dementia the onset is insidious and progressive over months to years. With delirium, attention and level of consciousness are reduced and fluctuating; with dementia these domains typically remain intact until the advanced stages of dementia.…”
Section: Distinguishing Delirium From Dementiamentioning
confidence: 99%
“…Third, to investigate whether a particular ROI was driving the effect for the association between the AD signature and delirium, separate regression models were performed for each of the 9 ROIs (average of left and right) that comprise the AD signature as well as a control region, calcarine cortex. Fourth, the association of AD signature with delirium outcomes was examined after controlling for several potential preoperative confounders: (1) preoperative cognitive function measured by baseline GCP score (Jones et al, 2016); (2) presence of aMCI to test whether observed relationships were driven by extreme phenotypes; (3) presence of vascular comorbidity (Gorelick et al, 2011; Schneider et al, 2002), and (4) presence of depression, which can exist simultaneously with or confer increased risk for both delirium and dementia (Downing et al, 2013). Finally, to reduce the influence of outliers, we Winsorized our data at the 98 th percentile, a commonly used approach to handling outliers that preserves their status but reduces the influence of extreme values (Thomas and Ward, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that depression is prevalent among patients with AD and MID, and that dementia represents a risk factor for depression in the elderly [51,52]. However, depression is often underdiagnosed in dementia patients due to overlapping motor deficits and cognitive impairment [53]. For instance, loss of interest and apathy are routinely mistaken for symptoms of psychomotor retardation rather than depression.…”
Section: Discussionmentioning
confidence: 99%